A miniaturized radiation monitor for continuous dosimetry and particle identification in space. (1st January 2022) - Gohl, St.; Malich, M.; Bergmann, B.; Burian, P.; Granja, C.; Heijne, E.; Holik, M.; Jacubek, J.; Janecek, J.; Marek, L.; Oancea, C.; Petro, M.; et al.
Abstract: A Miniaturized Radiation Monitor (MIRAM) has been developed for the continuous measurement of the radiation field composition and ionizing dose rates in near earth orbits. Compared to currently used radiation monitors, the presented device has an order of magnitude lower weight while being comparable in power consumption and functionality. MIRAM is capable of on-board real-time self-diagnostic. Furthermore, it supports on-board analysis of the measured data to be able to work autonomously. The dose rate is calculated continuously based on the energy deposition in the Timepix3 detector. For the estimation of the particle species composition of the radiation environment, two methods are applied depending on the current flux. At lower fluxes (<10 4 particles per cm 2 per s), a track-by-track analysis based on temporal coincidence is applied. At higher fluxes, a less power and memory consuming method is utilized. This method is using the averaged deposited energy per pixel to estimate the electron and proton content of the radiation field.